2013
DOI: 10.1089/ees.2013.0166
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Reaction Pathways of Waste Epoxy-Printed Circuit Board

Abstract: This article elucidates pyrolysis reaction pathways of waste epoxy-printed circuit boards (e-PCBs). Non-isothermal thermogravimetric analyses showed that waste e-PCBs decomposed via a series of reactions distinguished by three apparent reaction regions. The first-stage reaction ( <250°C) can be accounted for by the cleavage reaction of N-containing cross-linkage between brominated epoxy resin (BER) and non-brominated epoxy resin (NBER). Evolved gas analysis-mass spectrometry (EGA-MS) showed that the second-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…As well known, PCBAs are manufactured mainly with epoxy or phenol resin containing a fire retardant, such as tetrabromobisphenol-A (TBBPA) [32]. At a high combustion temperature (>400 • C in the rotary incinerator), the single bond between carbon atom and benzene ring in TBBPA may be broken or substituted by other radicals during the heating, releasing a large amount of AHs [33].…”
Section: Alteration Of Vocs Pollution Profiles Treated By Ep Technologymentioning
confidence: 99%
“…As well known, PCBAs are manufactured mainly with epoxy or phenol resin containing a fire retardant, such as tetrabromobisphenol-A (TBBPA) [32]. At a high combustion temperature (>400 • C in the rotary incinerator), the single bond between carbon atom and benzene ring in TBBPA may be broken or substituted by other radicals during the heating, releasing a large amount of AHs [33].…”
Section: Alteration Of Vocs Pollution Profiles Treated By Ep Technologymentioning
confidence: 99%
“…The TGA and derivative thermogravimetric curves (Figures 3 and 4) showed that the degradation temperature for the thermal breakdown of resins or paper laminate maximizes around 320°C in all cases. The first fast decomposition region ranges from 250°C to 350°C, peaking around 310–320°C, whereas the second slow decomposition region starts after 400°C, peaking around 500°C, which would represent the presence of components from FR-2 and FR-4 boards (Evangelopoulos et al, 2015; Kim et al, 2013, 2015). The NMFC shows a decomposition region from 350°C to 450°C, which represents the decomposition of phenolic resin.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have shown that the combustion of flame retardent-2 (FR-2) and flame retardant-4 (FR-4) type boards occurs in two distinct temperature ranges. A fast decomposition step of resins occurs from 250°C to 370°C, followed by a slow combustion process after 500°C (Evangelopoulos et al, 2015; Kim et al, 2013). The Fourier-transform infrared spectroscopy spectrum of the evolved products during the decomposition step shows the presence of low molecular weight compounds such as carbon monoxide, carbon dioxide, ammonia, hydrogen bromide, methane, and water molecules, and high molecular weight compounds such as phenol, dioxins, furans, benzene and their derivatives along with char residue.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors presented TBBA degradation mechanism and release of brominated compounds in their research (Grause et al, 2008; W. J. Kim et al, 2013). Moreover, Furans are highly toxic components and they are present in PCB oil in the form of Benzofuran, 2-isopropenyl-3-methyl-, Dibenzofuran, and 2(5H)-furanone, 3-hydroxy-4,5-dimethyl-(total of 1.44 % area) but their quantity decreased to 0.78 % area with co-pyrolysis, see Table 2.…”
Section: Liquid Analysismentioning
confidence: 99%
“…Additionally, it contains a large amount of volatile matter and lower O/C (Madhu et al, 2018); Kim et al, 2013) which gives an expectation of high bio-oil yield with improved quality (W. J. Madhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%